Calculation of Short-Circuit Current in DC Distribution System Based on MMC Linearization - Sun, Peixiao; Jiao, Zaibin; Gu, Hanwen (Frontiers in Energy Research, 2021)
The calculation of the short-circuit current is an important basis for fault detection and equipment selection in the DC distribution system. This paper proposes a linearized model for modular multilevel converter (MMC) considering different grounding methods and different failure scenarios. This model can be used in different fault conditions before MMC’s block. Under different fault forms, the model has different manifestations. This paper analyzes and models the DC distribution network with two types of faults: inter-pole short circuit and single-pole grounding short circuit. Among them, the modeling and analysis of single-pole grounding short-circuit uses the method of common- and differential-mode (CDM) transformation. To solve such a model, an analytical calculation method is proposed. As a mean of evaluating the effectiveness and accuracy of the proposed model, the analytical calculation solution is compared to the solution produced by PSCAD/EMTDC. A comparison of the results reveals the efficacy of the proposed model.